Effect of Package Type on Selected Parameters of Nutritional Quality of Chill-Stored White Sauerkraut - Kapusta-Duch Joanna; Kusznierewicz Barbara; Leszczyńska Teresa; Borczak Barbara (Polish Journal of Food and Nutrition Sciences)
Brassica vegetables, including white cabbage, both fresh and sour (Brassica oleracea L. var. capitata L.), contain a lot of valuable metabolites which are effective in chemoprevention of cancer as documented by numerous studies. This work investigates the effect of different packaging types; low density polyethylene (PE-LD) and metalized polyethylene terephthalate (PET met/PE) with polyethylene bags on selected quality parameters in chill-stored white sauerkraut. Sauerkraut was subjected to refrigerated storage for 4 months. Every month, stored sauerkraut was analyzed in terms of vitamin C, total phenolic compounds content and antioxidant activity. Statistical analysis demonstrated that the type of packaging had a significant influence on the antioxidant activity of chilled stored sauerkraut.